"Reversi‐type virologic failure" involved in the development of non‐structural protein 5A resistance‐associated variants (RAVs) in patients with genotype 1b hepatitis C carrying no signature RAVs at baseline. Issue 13 (19th April 2017) - Uchida, Yoshihito; Kouyama, Jun‐ichi; Naiki, Kayoko; Sugawara, Kayoko; Inao, Mie; Imai, Yukinori; Nakayama, Nobuaki; Mochida, Satoshi
Abstract : Aims: The therapeutic efficacy of daclatasvir/asunaprevir was inferior in patients with non‐structural protein 5A (NS5A)‐R30Q mutant hepatitis C virus strains at baseline, compared with those with wild‐type strains, even though the half maximal effective concentration of NS5A inhibitors was lower in mutant strains than in wild‐type strains. In these patients, R30Q and Y93H mutant strains, which are highly resistant to NS5A inhibitors, emerged at virologic failure. The mechanisms involved in such virologic failure were examined. Methods: The NS5A resistance‐associated variants were evaluated using direct sequencing in 88 patients with virologic failure after daclatasvir/asunaprevir therapy. In patients with R30Q and Y93H mutant strains at virologic failure, the original strains responsible for the multiple mutations were evaluated using baseline sera samples. Results: L28 M and/or R30Q, L31 M, and Y93H mutant strains were found in 36, 46, and 65 patients, respectively, and R30Q and Y93H mutants were seen in 23 patients. R30Q mutant strains were detected in baseline sera samples available from eight of these patients; cycling‐probe real‐time polymerase chain reaction showed that the Y93H mutant strain to total strain ratio was less than 1% in four patients and ranged from 1% to 98% in four patients. A phylogenetic tree analysis undertaken after deep sequencing revealed that the R30Q and Y93H mutant strains originated from minor strains with both mutations at baseline, even in patients with a ratio of less than 1%. Conclusion: In patients with genotype 1b hepatitis C virus strains with R30Q mutation, minor strains with Y93H as well as R30Q mutations contributed to the development of virologic failure after treatment with NS5A inhibitors.